Primary Intramedullary Hydatid cyst - Thapa, Ashish Jung; Tandon, Asheesh; Agrawal, Alok (Nepal Journal of Neuroscience, 2021)
Hydatid cysts or Hydatid disease is caused by Echinococcus granulosus infestation. Dogs, wolves, and other carnivores are the definitive host, and human being the accidental intermediate hosts. This disease commonly involves the liver and lungs and rarely involves other organs of the body. Primary intramedullary hydatid cysts are extremely rare and few cases before us have been reported in the literature. There is no pathognomonic sign or symptom for spinal hydatid cyst, mostly compression related symptoms, e.g. radiculopathy, myelopathy, local pain, and pathologic fractures are found. So preoperative diagnosis of spinal hydatid requires the correlation of all the aspects including clinical features, radiology, and lab reports.  Surgical management is the best treatment for spinal hydatid cyst with complete excision without cyst rupture being the primary target along with complete neural elements decompression. Here we report a case of a 26-year old male with paraparesis with MRI finding directing towards D9-D10 intramedullary cystic lesion (cystic astrocytoma) which was completely excised and histopathology report favored intramedullary hydatid cyst.